Has the publication of minutes helped markets to predict the monetary policy decisions of the Bank of England's MPC? - Makram El-Shagi; Alexander Jung (European Central Bank (ECB), 2015)
This paper examines whether the minutes of the Bank of England's Monetary Policy Committee (MPC) have provided markets with additional information about the future course of monetary policy. The paper conducts an econometric approach based on an Ordered Probit model explaining future policy rate changes (sample 1998 to 2014), and the Vuong test for model selection, which helps to identify changes in the market assessment around the release of MPC minutes. Our results suggest that the Bank of England's published minutes of the MPC's deliberations have indeed helped markets in forming their expectations on future monetary policy decisions.
Keywords: C34; D78; E52; E58; 330; Communication; monetary policy committee; MPC minutes; Probit; Vuong test